2020
DOI: 10.3389/fonc.2020.00444
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Integration Reveals a Competitive Endogenous RNAs Network for the Identification of Progression Biomarkers and the Stratification of Patients Diagnosed With Nephroblastoma

Abstract: Specific types of nephroblastoma (Wilms' tumor, WT) are known to associate with poor overall survival. Emerging experimental evidence has demonstrated that competitive endogenous RNA (ceRNA) networks have important roles in regulating cancer occurrence, but the roles of ceRNAs in regulating the WT progression and the patient outcomes remain unclear. Using the multi-omics data of 132 WT patients collected from TARGET database, an integration analysis pipeline was performed to construct a highly reliable ceRNA n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Five lncRNAs were consistently dysregulated in both datasets (Fig. 1B ), including ENSG00000238133, ENSG00000224079, ENSG00000249307 and ENSG00000224950, which were reported to correlate with human cancer progression [ 20 23 ]. Additionally, ENSG00000232415, termed LNMAS here, was significantly downregulated in the LNpos group, as determined by qPCR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Five lncRNAs were consistently dysregulated in both datasets (Fig. 1B ), including ENSG00000238133, ENSG00000224079, ENSG00000249307 and ENSG00000224950, which were reported to correlate with human cancer progression [ 20 23 ]. Additionally, ENSG00000232415, termed LNMAS here, was significantly downregulated in the LNpos group, as determined by qPCR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, the novel potential pharmacological effects of metformin and D -limonene were illustrated. Also, among these targets, the inducible nitric oxide synthase ( iNOS ) or type II genes correlated with carcinogenic processes in liver and breast cancers play a central role in inflammation and expresses protective effects against detrimental damage [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al combined expression data and survival analysis to identify two lncRNAs (HNF1A-AS1 and DELU2) that were significantly related to the overall survival time of WT patients, and may be used as novel prognostic markers for WT ( 46 ). Furthermore, Wang et al found that LINC00087 was significantly related to the overall survival rate of WT patients, and may become a prognostic biomarker of WT ( 113 ).…”
Section: Biologic Function Of Lncrnasin Wtmentioning
confidence: 99%